Scenarios for the future of the European legal sector, in the context of disruptive technologies, and its implications for the national association of young Portuguese lawyers (Anjap): framing, scoping & External environmental scanning - Bork, Alexandre (2021)
In the following Work Project, scenarios were developed based on scientific analysis and dealt with how the working environment of European lawyers could potentially develop in the future. The initial phases consisted of framing the focal issue, establishing a suitable time horizon, and performing an expert-examined external environment research. Then, a survey was conducted to build the foundational framework of scenarios and future strategies for the National Association of Young Portuguese Lawyers (ANJAP)